65 Immunological Changes in Response to Treatment of Bovine Respiratory Disease in Newly Received Commercial Stocker Calves. (8th October 2021) - Akter, Afroza; Shepherd, Elizabeth; Caldwell, Marc; Pighetti, Gina; Schneider, Liesel G
Abstract: Immunological changes in stocker calves treated for Bovine Respiratory Disease (BRD) could indicate disease progression or treatment success. Our objective was to determine the changes in immune parameters in stocker calves in response to the number of treatments they received for BRD. Forty newly weaned crossbred beef steers purchased from the auction market were kept at a commercial stocker operation at Crossville during winter 2020. Calves were monitored for 4wks and blood samples were collected on days 0, 7, 14, and 21. All calves were assigned a clinical severity scoring (CSS; 0: normal, 3: moribund) on each sampling day. Antibiotic treatment was assigned when calves were categorized as having BRD based on CSS and rectal temperature. Immune parameters (Haptoglobin, IL-8, IL-1β, and TNFα) were determined using commercial ELISA kits. Calves were categorized based on the cumulative number of treatments received by the end of study period (0x, 1x, and ≥2x). Proc GLIMMIX (SAS 9.4) was used to test the fixed effects of treatment number, day of treatment, and their interaction, accounting for day as a repeated measure. To achieve the normality of residuals, log transformation was performed. Significance was determined at α= 0.05. The incidence of BRD was 40% (16 out of 40). Haptoglobin concentration was higher (P = 0.02) in ≥2x (1.85 ± 0.30 mg/mL) compared to 0x (0.74 ± 0.21 mg/mL). A treatment by day interaction (P = 0.03) was observed for IL-8. On day 14, calves that were treated ≥2x times had higher IL-8 compared to the rest of the statuses; no differences were observed for other days between statuses. The lowest IL-1β (P = 0.04) and TNFα (P = 0.001) concentrations were observed on day 0. Results from this study provide an overview of the immunological changes occurring in BRD-affected stocker calves requiring different treatment numbers.